Combination of platelet count and neutrophil–lymphocyte ratio as a prognostic marker to predict chemotherapeutic response and survival in metastatic advanced gastric cancer. (October 2017) - Wang, Jin; Qu, Jinglei; Li, Zhi; Che, Xiaofang; Liu, Jing; Teng, Yuee; Jin, Bo; Zhao, Mingfang; Zhang, Lingyun; Liu, Yunpeng; Qu, Xiujuan
Aim: The study evaluated the prognostic impact of combination of platelet count and neutrophil–lymphocyte ratio (COP-NLR) for first-line chemotherapeutic response and survival outcomes in metastatic advanced gastric cancer patients.Methods: Two hundred and seventy-three patients were categorized into three COP-NLR groups (COP-NLR 0, 1, 2) according to their platelet count and neutrophil–lymphocyte ratio.Results: The COP-NLR 0 had a significantly higher disease control rate (93%) than the other two groups (p = 0.011). A logistic regression model showed that COP-NLR was an independent risk factor for response to chemotherapy (odds ratio: 2.247; 95% CI: 1.303–3.874; p = 0.044). The median overall survival for COP-NLR 0, 1 and 2 was 14.8, 10.3 and 9.1 months, respectively (p = 0.001).Conclusion: COP-NLR is a useful predictor of survival outcomes and chemotherapeutic response in patients with metastatic advanced gastric cancer.